2022
DOI: 10.1139/as-2020-0041
|View full text |Cite
|
Sign up to set email alerts
|

The tundra phenology database: more than two decades of tundra phenology responses to climate change

Abstract: Observations of changes in phenology have provided some of the strongest signals of the effects of climate change on terrestrial ecosystems. The International Tundra Experiment (ITEX), initiated in the early 1990s, established a common protocol to measure plant phenology in tundra study areas across the globe. Today, this valuable collection of phenology measurements depicts the responses of plants at the colder extremes of our planet to experimental and ambient changes in temperature over the past decades. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Phenological observations have been collected since 2001 by Yukon Parks Rangers on Qikiqtaruk every 2-3 days from April (snowmelt) until September (leaf senescence) along established transects (~ 250 m from our study site). The rangers record phenology throughout the growing season (Myers-Smith et al 2019) in line with ITEX protocol (Prevéy et al 2021). The phenological dates used in this study are the date of first leaf bud burst (leaf emergence) and the date of first yellowing of leaves (leaf senescence) averaged across the 20 S. arctica individuals in the observation transect.…”
Section: Phenology Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Phenological observations have been collected since 2001 by Yukon Parks Rangers on Qikiqtaruk every 2-3 days from April (snowmelt) until September (leaf senescence) along established transects (~ 250 m from our study site). The rangers record phenology throughout the growing season (Myers-Smith et al 2019) in line with ITEX protocol (Prevéy et al 2021). The phenological dates used in this study are the date of first leaf bud burst (leaf emergence) and the date of first yellowing of leaves (leaf senescence) averaged across the 20 S. arctica individuals in the observation transect.…”
Section: Phenology Datamentioning
confidence: 99%
“…The Arctic is warming three to four times faster than the rest of the planet (Meredith et al 2019;You et al 2021) and tundra plant communities are particularly sensitive to that warming (Elmendorf et al 2015;Bjorkman et al 2020). Climate change is resulting in a longer snow-and ice-free season, potentially facilitating longer growing seasons (Cleland et al 2007;Khorsand Rosa et al 2015;Prevéy et al 2021;Frei and Henry 2021). Concurrent with these changes, shifts in distribution and abundance (Sturm et al 2001;Elmendorf et al 2012a), biomass (Hudson and Henry 2009), and phenology (timing of life history events) (Oberbauer et al 2013) have been observed for species across the tundra.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forage quality responses to warming involve multiple processes that operate on different time scales. Nearly all plant growth is influenced by cumulative heat (i.e., growing degree days) that critically influences the maturation and phenology of key seasonal activities such as budburst and flowering (Collins et al, 2021; May et al, 2020; Prevéy et al, 2022). The cumulative heat effect of warming should drive immediate‐ to short‐term responses in forage quality.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is resulting in a longer snow-and ice-free season, potentially facilitating longer growing seasons (Cleland et al 2007;Khorsand Rosa et al 2015;Prevéy et al 2021;Frei and Henry 2021). Concurrent with these changes, shifts in distribution and abundance (Sturm et al 2001;Elmendorf et al 2012a), biomass (Hudson and Henry 2009), and phenology (timing of life history events) (Oberbauer et al 2013) have been observed for species across the tundra.…”
Section: Introductionmentioning
confidence: 99%